The Uslub of Tafsir Al-Quran - Alawi, Asep Habib Idrus (Journal of Islamicate Studies, 2018)
This article discusses the method of interpreting the Qur'an. After tracking bibliographic sources, it was found that the differences between the commentators of the Qur'an in the use and meaning of the terms manhaj and uslub. According to this study, the correct one, the term used for the Interpretation of Ta?l?l?, Ijm?l?, Maw??'? and Muq?ran is usl?b not manhaj. Usl?b Tafs?r Ta?l?l? is a systematic system used by an interpreter in interpreting the Koran following the order of verses and letters in the Mu??af, both in whole or in many verses or letters. Then in each verse explained everything related to the verse, for example, the meaning of the word, the sense of stylist, asb?b al-nuz?l, the laws contained, and the importance of the whole verse. Usl?b Tafs?r Ijm?l? is a work of commentator who adheres to the arrangement of verses that are grouped. Then, explained the general meaning or the whole verse under what is desired by the editorial verse. Usl?b Tafs?r Muq?ran is collecting and comparing the ulama's two interpretations or more about the verses of the Koran, studying them, and concluding which interpretations are the most powerful. Usl?b Tafs?r Maw??'? is systematic writing of understandings used by an interpreter by not following the order of verses in the Koran, but by collecting all the verses that speak the same theme, then explain and take legal conclusions.